Estudo da viabilidade técnica do uso das argilas da região do agreste potiguar para produção de peças cerâmicas: caracterização e formulação - Monteiro, Flanelson Maciel (2012)
In recent decades, ceramic products have become indispensable to the technological development of humanity, occupying important positions in scientific production and consequently in industrial production. One area of the economy that continues to absorb large amounts of the products of this sector is Construction. Among the branches of the ceramic industry, there are the red ceramic industry which is traditionally the basis of that economic sector. Among the reasons for which the red ceramic industry became popular in the country, and specifically in Rio Grande do Norte, is the abundance of this raw material, easily found throughout the national territory. However, it appears that the red ceramic industry has deficiencies in technology and skilled labor, resulting in the production of ceramic goods with low added value. Among the factors that determine the quality of the ceramic products red has the proper formulation of the ceramic mass, the conformation and the firing temperature. Thus, the overall goal of this work is to study the mineralogical and technological properties, two clays from the region of the Wasteland Potiguar industrial ceramist. Therefore, the raw materials were characterized by analysis of Xray diffraction (XRD) analysis, X-ray fluorescence (XRF), particle size analysis (FA), scanning electron microscopy (SEM), optical microscopy (OM ), plasticity index (PI), thermal gravimetric analysis (TGA) and differential thermal analysis (DTA). The technological properties of the material were analyzed by water absorption tests (AA%) porosity (% PA), the linear shrinkage (RT%), apparent density (MEA), loss on ignition (PF%) and flexural strength three points (TRF)